Sifat Kimia dan Nilai Biologis Konsentrat Protein Bungkil Inti Sawit Hasil Ekstraksi Kombinasi Fisik-Kimiawi - . Yatno; N Ramli; P Hardjosworo; A Setiyono; T Purwadaria (Media Peternakan, 2008)
The experiment was conducted to evaluate chemical characteristics and biological value of protein concentrate extracted from palm kernel meal (PKM) using combination of physical and chemical extraction. The best method of extraction in term of total amino acid (TAA), essential amino acid (EAA), essential amino acid index (EAAI), and protein recovery then was used for protein retention evaluation using 20 heads of male quails age 30 days. The animals were randomly assigned to one of three dietary treatments, while the remaining quails were used to measure endogenous protein. The treatments were; R1=diet containing 9% crude protein from the best protein concentrate from PKM, R2=diet containing 9% crude protein from PKM and R3=diet containing 9% crude protein from soybean meal). The results showed that protein of PKM had isoelectric pH in a range of 4.3-4.4. Protein concentrate of PKM produced by grinding using 0.05 N acetic acid followed by soaking 1 N technical-NaOH had the highest protein quality compared with those of the other treatments. TAA, EAA, EAAI amount of precipitate and protein recovery of the protein concentrate were 33.38%, 16.76%, 62.41%, 12.18% and 50.38%, respectively. Protein retention of quails fed R1 was not different compared to that of R3 (69,82 vs 70,57%), while quails received R2 had the lowest protein retention value (61,19%). It is concluded that combination methods of physical and chemical extraction using 0.05 N acetic acid followed by soaking with 1 N technical NaOH (E3) was the best method in producing high quality of protein concentrate, and the product had similar protein retention value as that of soybean meal. Key words: chemical characteristics, biological value, protein concentrate, palm kernel meal, extraction